(untitled) (Research, Society and Development, 2021)
The severity and incidence of Clostridioides difficile infection (CDI) have increased over the last decade. Cancer predisposes patients to CDI due to increased exposure to risk factors. The present study aimed to determine the prevalence, clinical response, outcomes, risk factors as supported in the literature in cancer patients with CDI. This was a prospective cross-sectional study conducted at two reference centres in oncology in Recife-PE, Brazil and involved individuals aged ≥18 years who presented with diarrhoea 48 hours after hospital admission, from November 2017 to August 2019. CDI was diagnosed using real-time polymerase chain reaction (qRT-PCR). A total of 156 patients were included in the study, and CDI was detected in 7.05% (11/156) of the patients. All isolates were screened, and the DNA was isolated and amplified by qRT-PCR for the detection of genes coding for toxins A and B (tcdA and tcdB), binary toxin (cdtA), and triose phosphate isomerase (tpi). Breast cancer and acute lymphoid leukemia were the most frequent cancers (27.3% [3/11] and 18.2% [2/11], respectively); 90.9% (10/11) of the cases used antibiotics, and the mortality rate was 63.6% (7/11 patients). Despite the use of the qRT-PCR technique, which is the most sensitive and specific method for diagnosing CDI, it was found that the prevalence of the disease was low (7.05%; 11/156). There were no cases of severe CDI, and most cases found were mild, which suggests the circulation of strains with low virulence that determine lower morbidity and mortality.